A case of dedifferentiated liposarcoma showing a biphasic pattern on 2-deoxy-2-F18- fluoro-D-glucose positron emission tomography/ computed tomography - Manabu Hoshi (Rare Tumors, 2013)
Integrated 2-deoxy-2-F18-fluoro-D-glucose positron emission tomography combined with computed tomography (FDG-PET/CT) has been used in the field of soft tissue sarcoma. We report an 81-year-old man with dedifferentiated liposarcoma in the left thigh, which was composed of well-differentiated liposarcoma and pleomorphic malignant fibrous histiocytoma. As well as other radiological modalities, FDG-PET was able to demonstrate a biphasic signal pattern composed of well-differentiated liposarcoma and dedifferentiated area, being consistent with the histological grade of malignancy.